The mediating role of spiritual intelligence in the relationship between media literacy and tendency to addiction in nursing students - Elahe Golrang; Qamar Kiani; Afsaneh Sobhi (Preventive Care in Nursing and Midwifery Journal, 2023)
Background: Drug abuse among students is a widespread issue that can have negative consequences on their psychological well-being and academic performance. Objectives: This study aims to investigate the mediating role of spiritual intelligence in the relationship between media literacy and tendency to addiction in nursing students in 2022. Methods: The research involved 139 undergraduate nursing students from Zanjan and Abhar School of Nursing and employed non-random quota sampling. Data were collected using questionnaires assessing addiction tendency, media literacy, and spiritual intelligence. The analysis, conducted in SPSS 24, included Pearson's correlation coefficient and regression analysis following Baron and Kenny's mediation method. Results: The results revealed significant negative correlations between addiction tendency and both media literacy (r=-0.33) and spiritual intelligence (r= -0.36). Mediation analysis demonstrated that spiritual intelligence played a significant mediating role in the relationship between media literacy and addiction tendency. The path from media literacy to spiritual intelligence was significant (β= 0.28), as was the path from spiritual intelligence to addiction (β= -0.36). Furthermore, the total effect of media literacy on addiction (β= -0.16) and the direct effect of media literacy on addiction with the inclusion of spiritual intelligence in the model (β= -0.21) were both significant, confirming the mediating role of spiritual intelligence. Conclusion: this study underscores the mediating role of spiritual intelligence in the relationship between media literacy and addiction among nursing students. These findings emphasize the importance of incorporating media literacy and spiritual intelligence into nursing education to potentially reduce the risk of addiction among students.